School choice in a quasi-market system mediated by the bilingual program - Murillo, F. Javier; Almazán, Adrián; Martínez-Garrido, Cynthia (Revista Complutense de Educación, 2021)
Introduction. This research seeks to understand the reasons that guide the choice of school by families whose children study at public schools of the Community of Madrid. Special emphasis is made on approaching the role played by bilingual schools within the general issues associated with school choice. Method. In order to achieve our aim, a qualitative research is carried out based on semi-structured interviews. The participants are 14 representatives of different Parents Associations from Public Infant and Primary Schools, as well as from High schools –half of them bilingual– within the municipality of Getafe (Region of Madrid, Spain). Results. The affiliation or non-affiliation of the school to the bilingual program has radically altered the school selection criteria by families in recent years. As a result, the proximity to the school and the social perception of the school’s quality have become the most important factors of choice. In the case of belonging to the bilingual programme, it implies as many criticisms as adhesions, with strong rejection by families in many cases due to the segregation it is generating. Discussion. The bilingual programme and the emergence of the single school district is generating a strong polarisation of society that intensifies the segregation of the education system. It seems, necessary to rethink the measures of free choice and handle a global and independent evaluation of the bilingual programme.